2012
DOI: 10.1149/2.006205jes
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cycling Performance of Lithium Ion Cell Anode Graphites

Abstract: Battery grade graphite products from major suppliers to the battery industry were evaluated in 2325 coin cells with lithium counter electrodes. First and subsequent cycle efficiency, discharge capacity, and discharge rate performance were measured to compare these anode materials. A formula has been developed to utilize lithium ion battery cycling performance data to estimate the overall battery cost, relative to the cost of a battery using MCMB. This analysis indicates that replacing MCMB with CPG-8 (Conoco P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…This material has been previously characterized in the literature. 22 The model also assumes a uniform particle size. Therefore, the as received powder was sieved (Advantech Manufacturing) to obtain a narrow particle size distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This material has been previously characterized in the literature. 22 The model also assumes a uniform particle size. Therefore, the as received powder was sieved (Advantech Manufacturing) to obtain a narrow particle size distribution.…”
Section: Methodsmentioning
confidence: 99%
“…26,36 Our results in this work are only comparable to what has been reported for carbon nanospheres prepared by carbonizing polypyrrole nanospheres. 35 This exceptional cyclic performance for RF derived carbon xerogel nanoparticles may be attributed to facile diffusion between interconnected particles due to smaller diffusion length (radius of gyration 2.46 nm) and adsorption of lithium on the nanopores formed by small crystallites arrangement like house of cards with small in-plane crystallite thickness and mean stack height of crystallite as shown by XRD and Raman spectra. These results clearly indicate the superior electrochemical behaviour of as-prepared RF derived carbon xerogel nanoparticles even as compared to graphite which is most widely used anode material in commercial Li ion battery.…”
Section: Galvanostatic Charge/discharge Experimentsmentioning
confidence: 99%
“…Rempel et al [12], Xue et al [25], and Nelson et al [10] have suggested that electrode coating thickness plays a major role on cost. While numerous articles are dealing with the technical effects of thick or thin electrodes [26][27][28][29][30][31][32][33][34][35][36], none are dedicated to the study of the effects on cost.…”
Section: Introductionmentioning
confidence: 99%